Description of a new species of cecidomyiid (Diptera: Cecidomyiidae) predator of mealybugs (Hemiptera: Pseudococcidae) on sugarcane - Urso-Guimarães, Maria Virgínia; Cruz, Maiara Alexandre; Martinelli, Nilza Maria; Peronti, Ana Lúcia Gonzalez Benfatti (Papéis Avulsos de Zoologia, 2020)
Diadiplosis saccharum sp. nov. (Diptera: Cecidomyiidae) is described based on male and female prey on nymphs of mealybug Saccharicoccus sacchari (Cockerell) (Hemiptera: Pseudococcidae) on Saccharum spp. (Poaceae) in São Paulo State, Brazil. Herein, the genus is composed by 33 species. The key of the eight species of the Diadiplosis distributed in Brazil is updated.